2016
DOI: 10.1007/s13361-016-1422-0
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Recrystallization for MALDI-MS Imaging of Maize Lipids at High-Spatial Resolution

Abstract: Abstract. Matrix recrystallization is optimized and applied to improve lipid ion signals in maize embryos and leaves. A systematic study was performed varying solvent and incubation time. During this study, unexpected side reactions were found when methanol was used as a recrystallization solvent, resulting in the formation of a methyl ester of phosphatidic acid. Using an optimum recrystallization condition with isopropanol, there is no apparent delocalization demonstrated with a transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…We successfully applied this recrystallization strategy to plant tissues with DAN as a matrix and demonstrated no delocalization was present at 10 mm spatial resolution. [66] Recrystallization with 5 % isopropyl alcohol at 55 8C for 2 minutes was most optimal and increased ion signals by three times when applied to the imaging of maize leaves. More importantly, we found methanol was not a good recrystallization solvent due to side reactions with phosphatidic acids, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 indicating some care must be taken when using recrystallization methods.…”
Section: Matrix Recrystallization Of Lipids For High-spatial Resolutionmentioning
confidence: 98%
See 1 more Smart Citation
“…We successfully applied this recrystallization strategy to plant tissues with DAN as a matrix and demonstrated no delocalization was present at 10 mm spatial resolution. [66] Recrystallization with 5 % isopropyl alcohol at 55 8C for 2 minutes was most optimal and increased ion signals by three times when applied to the imaging of maize leaves. More importantly, we found methanol was not a good recrystallization solvent due to side reactions with phosphatidic acids, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 indicating some care must be taken when using recrystallization methods.…”
Section: Matrix Recrystallization Of Lipids For High-spatial Resolutionmentioning
confidence: 98%
“…It has been demonstrated that a recrystallization step can enhance the sensitivity of proteins without inducing delocalization of analytes, but this has been demonstrated only for animal tissues. We successfully applied this recrystallization strategy to plant tissues with DAN as a matrix and demonstrated no delocalization was present at 10 μm spatial resolution . Recrystallization with 5 % isopropyl alcohol at 55 °C for 2 minutes was most optimal and increased ion signals by three times when applied to the imaging of maize leaves.…”
Section: Development Of New Matrices For High‐spatial Resolution Imagingmentioning
confidence: 99%
“…A study on maize embryo imaging by MALDI‐MS reported that the ions at m/z 685.4 and 709.4 are methyl phosphoesters of PA 34:2 ( m/z 671.4) and PA 36:4 ( m/z 695.4), respectively. It was also mentioned that the phosphoesterification of phosphatidic acid was detected only when 5% methanol was used as the solvent for matrix recrystallization …”
Section: Resultsmentioning
confidence: 99%
“…Sublimation of the matrix onto the sample to be analyzed has been widely used, but typically requires a conditioning or recrystallization step to promote analyte incorporation . This conditioning has been performed with different solvents and parameters and shown to potentially introduce unexpected side reactions . Microspotting of matrices directly onto tissues has also been performed but results in a heterogeneous matrix overlayer as compared to those produced with sublimation or spraying of matrix solution …”
mentioning
confidence: 99%
“…[22,23] This conditioning has been performed with different solvents and parameters and shown to potentially introduce unexpected side reactions. [24] Microspotting of matrices directly onto tissues has also been performed [25] but results in a heterogeneous matrix overlayer as compared to those produced with sublimation or spraying of matrix solution. [2] In the context of conventional MALDI sample preparation, electrospray deposition (ESD) has been shown to produce highly homogenous and reproducible samples.…”
mentioning
confidence: 99%